Strategi Pencegahan Cybercrime pada Data Pribadi di Media Sosial - Dinda Munifah Marpaung (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of information and communication technology in the digital era has a significant impact on the protection of personal data on social media. Rapid digitization not only facilitates data distribution and storage, but also increases the risk of cybercrime such as data theft, hacking, phishing and cyberbullying. This study aims to analyze effective prevention strategies in protecting personal information on social media. Using a qualitative approach through literature studies, questionnaires, as well as data analysis from trusted sources such as scientific journals and articles accessed through Google Scholar and Mendeley, this research found that users' awareness of personal data security is still low. The results show that many users have not implemented adequate preventive measures, such as changing passwords regularly or utilizing security features provided by social media platforms. Proposed prevention strategies include user education, strong password enforcement, account privacy settings, and increased awareness of cyber threats.